Pre-aged sodium nickelate cathode materials and uses thereof

By desodium and pre-aging the nickelate material, the chemical and thermodynamic instability of high-priced nickel cathode materials are solved, and the battery shelf life is extended and the electrochemical performance is improved.

CN119497702APending Publication Date: 2025-02-21ENERGIZER BRANDS LLC +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380032781.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-15
Filing Date
2023-04-17
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The high-priced nickel cathode materials in existing alkaline electrochemical cells are chemically unstable, resulting in limited shelf life and thermodynamic instability, resulting in electrochemical reduction and electrode capacity loss.

Method used

Desodiumed nicate material is used and its stability is improved by pre-aging treatment. A specific method includes contacting sodium nitrite with an acid solution to desodium and subsequently contacting a pre-aging solution containing hydroxide to produce a pre-aging nickel material with improved chemical stability.

Benefits of technology

Through pre-aging treatment, the chemical stability and electrochemical performance of the nicate material are improved, the shelf life of the battery is extended, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005072694040000211
    Figure BDA0005072694040000211
  • Figure BDA0005072694040000212
    Figure BDA0005072694040000212
  • Figure BDA0005072694040000221
    Figure BDA0005072694040000221
Patent Text Reader

Abstract

Provided herein are de-sodium, pre-aged sodium nickelate that has been de-sodium by acid leaching and has been pre-aged using a hydroxide solution. The sodium removed, pre-aged, sodium nickelate exhibits improved stability. Also provided herein are mixtures of such nickelate and EMD and methods of making such sodium nickelate as well as alkaline electrochemical cells comprising such nickelate.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Application Serial No. 63 / 363,064, filed on April 15, 2022, which is hereby incorporated by reference in its entirety for all of its teachings. Background Art

[0003] Alkaline electrochemical cells are commercially available in cell sizes commonly referred to as LR6 (AA), LR03 (AAA), LR14 (C), and LR20 (D). The cylindrical shape of the cell must conform to dimensional standards established by organizations such as the International Electrotechnical Commission. The electrochemical cells are used by consumers to power a variety of electrical devices, such as clocks, radios, toys, electronic games, film cameras that typically include flash units, and digital cameras. Such electrical devices have a variety of discharge conditions, such as from low drain to relatively high drain.

[0004] Since the shape and size of batteries are generally fixed, battery manufacturers must modify battery cell characteristics to improve performance. Attempts to solve the problem of how to improve battery performance in a particular device, such as a digital camera, often involve changing the internal construction of the battery cell. For example, the battery cell construction has been modified by increasing the amount of active material used within the battery cell.

[0005] High-valent nickel materials including nickel oxyhydroxide (NiOOH), nickel dioxide (NiO2), and various forms of nickel oxide, nickelate, and nickel oxyhydroxide can be used as cathode materials in alkaline systems due to their high capacity and cell voltage. x The oxidation state of NiO2 (where x<<1) is higher than 3+, which potentially enables a much higher discharge capacity than that of EMD (MnO2). x NiO2 is chemically unstable and degrades rapidly at high temperatures. In addition, these materials are thermodynamically unstable in aqueous electrolytes, which results in electrochemical reduction of the nickel cathode (loss of electrode capacity). Therefore, the shelf life of alkaline batteries with high-priced nickel cathodes is limited compared to batteries containing some other cathode materials. Summary of the invention

[0006] One embodiment of the present invention is a sodium-removed nickelate material, the cathode material having an X-ray diffraction (XRD) pattern, the XRD pattern including a first peak of about 11.9°-14°2θ, a second peak set of about 18°-22°2θ, a third peak of about 36.1°-38.6°2θ, a fourth peak of about 41°-44.2°2θ, a fifth peak of about 55.7°-58.9°2θ, a sixth peak of about 65°-67.3°2θ, and a seventh peak of about 69.5°-71.3°2θ. In an alternative embodiment, the sodium-removed nickelate material has an XRD pattern, the XRD pattern having at least 1, 2, 3, 4, 5, 6, or 7 of the seven peaks or peak sets. In one embodiment, the sodium-removed nickelate material has an XRD pattern, the XRD pattern having a peak of about 69.5°-71.3°2θ.

[0007] One embodiment is a sodium-desorbed nickelate material, the cathode material having an X-ray diffraction (XRD) pattern, the XRD pattern including a first peak of about 11.3°-14.6°2θ, a second peak set of about 17.3°-22.3°2θ, a third peak of about 23.8°-25.9°2θ, a fourth peak of about 27.2°-28.2°2θ, a fifth peak of about 36.2°-37.7°2θ, a sixth peak of about 40°-44°2θ, a seventh peak of about 55.7°-58.5°2θ, an eighth peak of about 65.2°-67.3°2θ, and a ninth peak of about 69.5°-71.1°2θ. In an alternative embodiment, the desodiumated nickelate material has an XRD pattern having at least 1, 2, 3, 4, 5, 6, 7, 8 or 9 of these nine peaks or sets of peaks.

[0008] One embodiment is a pre-aged, de-sodiumed nickelate material having an X-ray diffraction (XRD) pattern including a first peak at about 11.9°-13.8°2θ, a second peak at about 17°-19.5°2θ, a third peak at about 24.7°-26.5°2θ, a fourth set of peaks at about 36.3°-39.2°2θ, a fifth set of peaks at about 41.9°-45.7°2θ, a sixth peak at 47.5°-49.5°2θ, a seventh peak at about 50.3°-52°2θ, an eighth peak at about 57.4°-58.7°2θ, and a ninth set of peaks at about 65°-68°2θ. In an alternative embodiment, the desodiumed nickelate material has an XRD pattern having at least 1, 2, 3, 4, 5, 6, 7, 8, or 9 of these nine peaks or sets of peaks. In an embodiment, the desodiumed nickelate material has an XRD pattern having a peak at about 50.3°-52° 2θ.

[0009] One embodiment is a pre-aged, de-sodiumed nickelate material having an X-ray diffraction (XRD) pattern including a first peak at about 11.1°-14.4°2θ, a second set of peaks at about 17.2°-19.9°2θ, a third peak at about 24.1°-26.0°2θ, a fourth set of peaks at about 35.8°-39.3°2θ, a fifth set of peaks at about 43.4°-45.4°2θ, a sixth peak at 47.7°-49.4°2θ, a seventh peak at about 56.8°-59.6°2θ, an eighth peak at about 62.8°-64.5°2θ, a ninth peak at about 65°-67.4°2θ, and a tenth peak at about 68.1°-69.2°2θ. In an alternative embodiment, the desodiumated nickelate material has an XRD pattern having at least 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 of these ten peaks or sets of peaks.

[0010] One embodiment is a method of producing a pre-aged, desodiumated nickelate material, the method comprising:

[0011] i) contacting the sodium nickelate with an acid solution to produce an acid-leached, de-sodiumed nickelate; and

[0012] ii) contacting the acid-leached desodiumated nickelate with a pre-aging solution comprising a hydroxide,

[0013] To produce the pre-aged, desodiumated nickelate material.

[0014] One embodiment is a pre-aged, desodiumated nickelate material prepared by any of the methods described herein.

[0015] One embodiment is an alkaline cathode composition comprising any of the pre-aged, desodiumated nickelate materials described herein and electrolytic manganese dioxide (EMD).

[0016] One embodiment is an alkaline cathode composition comprising any of the pre-aged, desodiumated nickelate materials described herein, electrolytic manganese dioxide, graphite, and a binder.

[0017] One embodiment is a sodium-deionized nickelate material comprising the following phases:

[0018] i) 15-50 wt% NiO2;

[0019] ii) 20-60 wt% of β-NiOOH;

[0020] iii) 0-25 wt% H 0.61 NiO2(H2O) 0.91;as well as

[0021] iv) 0-25 wt% Na 0.33 NiO2(H2O) 0.54 .

[0022] One embodiment is a sodium-deionized nickelate material having the formula Na x NiO2(H2O) z , wherein x = 0.01-0.05, and z = 0.2-1.1. In one embodiment, x is at least, at most, or about 0.01, 0.02, 0.03, 0.04, or 0.05, or within a range defined by any two of these values. In one embodiment, z is at least, at most, or about 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or 1.1, or within a range defined by any two of these values.

[0023] One embodiment is a nickelate material comprising the following phases:

[0024] i) 4-62 wt% Na 0.33 NiO2(H2O) 0.54 ;

[0025] ii) 30-80 wt% (Li 0.39 Ni 0.01 )(NiO2) and / or (Li 0.49 Ni 0.01 )(NiO2) and / or (Li 0.45 Ni 0.05 )(NiO2); and

[0026] iii) 0-50 wt% of β-NiOOH.

[0027] One embodiment is a nickelate material comprising the following phases:

[0028] i) 80-85 wt% Na 0.33 NiO2(H2O) 0.54 ;as well as

[0029] ii) 15-20 wt% of β-NiOOH.

[0030] One embodiment is a nickelate material having the formula Na x Li y NiO2(H2O) z, wherein x = 0.01-0.05, y = 0.15-0.45, and z = 0.1-0.8. In one embodiment, x is at least, at most, or about 0.01, 0.02, 0.03, 0.04, or 0.05, or within a range defined by any two of these values. In one embodiment, y is at least, at most, or about 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, or 0.45, or within a range defined by any two of these values. In one embodiment, z is at least, at most, or about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, or 0.8, or within a range defined by any two of these values.

[0031] One embodiment is a nickelate material that exhibits three discharge plateaus relative to a Zn / ZnO reference electrode during discharge at a discharge rate of 10 mA / g to a voltage of 1.0 V.

[0032] One embodiment is a composition comprising particles comprised of a nickelate material, wherein the particles comprise:

[0033] i) an inner core comprising a nickelate that has not been pre-aged with a hydroxide; and

[0034] ii) an outer layer comprising a nickelate that has been pre-aged with a hydroxide.

[0035] One embodiment is an alkaline electrochemical cell comprising any of the nickelate materials or compositions described herein. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a cross-sectional elevation view of an alkaline electrochemical device according to one embodiment.

[0037] Figure 2 An X-ray diffraction (XRD) pattern of sodium nickel oxide is shown.

[0038] Figure 3 An X-ray diffraction (XRD) pattern of acid-treated sodium nickel oxide is shown.

[0039] Figure 4 Shown is the X-ray diffraction (XRD) pattern of acid-treated NaNiO2 powder aged in 40wt% KOH / 6wt% ZnO for 24 hours.

[0040] Figure 5 The Na pre-aged with LiOH x X-ray diffraction (XRD) pattern of NiO2.

[0041] Figure 6The LiOH pre-aged Na2O2 in 40 wt% KOH / 6 wt% ZnO after aging for 24 h is shown. x X-ray diffraction (XRD) pattern of NiO2.

[0042] Figure 7 Shown is a comparison of the specific capacities at 1 V of the EMD, non-pre-aged nickelate, and LiOH-pre-aged nickelate after half-cell aging at 60°C for 0, 3, 7, and 14 days.

[0043] Figure 8 Shown are discharge curves at 10 mA / g for the non-pre-aged nickelate and the LiOH-pre-aged nickelate before and after aging in 40 wt % KOH / 6 wt % ZnO for 24 hours.

[0044] Fig. 9 Shown is a comparison of the specific capacity at 1 V of the EMD mixed 0.1 M LiOH / 1 minute pre-aged nickelate and the nickelate without pre-aging.

[0045] Fig.10 Shown is a comparison of the efficiency to 1 V of the EMD mixed 0.1 M LiOH / 1 minute pre-aged nickelate and the nickelate without pre-aging.

[0046] Fig.11 Shown is the XRD pattern of the as-synthesized nickelate without pre-aging.

[0047] Fig.12 The XRD pattern of the synthesized LiOH pre-aged nickelate is shown.

[0048] Fig.13 XRD patterns of alpha nickelate, beta nickelate, and sodium nickelate are shown.

[0049] Fig.14 Rietveld analysis of the XRD pattern of nickelate I without pre-aging (de-sodiumized NaNiO2) for phase quantification is shown.

[0050] Fig.15 Rietveld analysis of the XRD pattern of nickelate II without pre-aging (de-sodiumated NaNiO2) for phase quantification is shown.

[0051] Fig.16 Shown is a Rietveld analysis of the XRD pattern of pre-aged nickelate I (0.1 M LiOH, 1 min) derived from non-pre-aged nickelate I for phase quantification.

[0052] Fig.17Shown is a Rietveld analysis of the XRD pattern of pre-aged nickelate II (0.1 M LiOH, 1 min) derived from non-pre-aged nickelate II for phase quantification.

[0053] Fig.18 Rietveld analysis of the XRD pattern of the pre-aged nickelate (0.5 M LiOH, 10 min, from Example 4) is shown for phase quantification.

[0054] Fig.19 Rietveld analysis of the XRD pattern of the pre-aged nickelate (0.1 M LiOH, 10 min, from Example 4) is shown for phase quantification.

[0055] Fig. 20 A comparison of the discharge characteristics of α-nickelate, β-nickelate, and desodiumated NaNiO2 to 1.5 V before and after pre-aging in 0.1 M LiOH for 1 minute is shown.

[0056] Fig.21 A comparison of the discharge characteristics of α-nickelate, β-nickelate, desodiumed NaNiO2 before and after pre-aging in 0.1 M LiOH for 1 minute to 1.0 V is shown, as well as a depiction of the three discharge regions discussed in more detail below.

[0057] Fig. 22 A schematic diagram of a representative sodium nickelate particle is shown, having an inner core that has not been pre-aged and an outer layer that has been pre-aged. DETAILED DESCRIPTION

[0058] Various embodiments will now be described more fully below with reference to the accompanying drawings, in which some but not all embodiments are shown. In fact, various embodiments can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein; on the contrary, these embodiments are provided so that the present disclosure will satisfy applicable legal requirements. Throughout the text, the same reference numerals refer to the same elements. In the following description, each component can be identified as having a specific value or parameter; however, these items are provided as exemplary embodiments. In fact, the exemplary embodiments do not limit the various aspects and concepts of the embodiments, because many comparable parameters, sizes, ranges and / or values ​​can be implemented. The terms "first", "second", etc., "primary", "exemplary", "minor", etc. do not represent any order, quantity or importance, but are used to distinguish one element from another element. Further, the terms "one (a)", "an" and "the" do not represent a limitation on quantity, but represent that there is "at least one" referenced item.

[0059] This embodiment is designed in an effort to overcome the limitations of existing electrochemical cells. Typically, Na2O2 produced by acid leaching x The capacity of NiO2 is higher than that of Li x NiO2 has lower capacity and poorer stability than beta-nickelate.A pre-aging method is disclosed that improves the chemical stability of sodium nickelate materials at high temperatures.

[0060] It is contemplated that each embodiment disclosed herein is applicable to each of the other disclosed embodiments.All combinations and sub-combinations of the various elements described herein are within the scope of the embodiments.

[0061] It should be understood that where a parameter range is provided, the embodiments also provide all integers and ranges within the range, as well as tenths and hundredths thereof. For example, "5-10%" includes 5%, 6%, 7%, 8%, 9% and 10%; 5.0%, 5.1%, 5.2%, ... 9.8%, 9.9% and 10.0%; and 5.00%, 5.01%, 5.02%, ... 9.98%, 9.99% and 10.00%, and, for example, 6-9%, 5.1%-9.9% and 5.01%-9.99%.

[0062] As used herein, "about" in the context of a numerical value or a range means within ±10%, ±5%, or ±1% of the recited or claimed numerical value or range.

[0063] As used herein, "nickelate" refers to a salt containing a nickel-containing anion, or a compound including nickel and at least one other element in combination with oxygen.

[0064] As used herein, "nickel compound" refers to any compound including nickel. "Nickel material" refers to any material including nickel.

[0065] As used herein, "sodium nickelate material" or "sodium nickelate compound" refers to any nickelate salt including sodium. Non-limiting examples include Na x NiO2, of which 0 <x≤1。

[0066] As used herein, "desodiumated nickelate" refers to a nickel compound obtained when some or all of the sodium of a sodium-containing nickel compound is removed.

[0067] As used herein, "oxide" refers to a chemical compound containing at least one oxygen atom and one other element. As used herein, "nickel oxide" refers to any oxide containing nickel. Nickel oxide may include other cations and anions. Non-limiting examples include nickel dioxide (NiO2), nickel hydroxide (Ni(OH)2), and hydrated alkaline nickel oxide (such as Nax NiO2·n(H2O)).

[0068] As used herein, "oxyhydroxide" refers to a chemical compound or complex containing an oxide group and a hydroxide group. As used herein, "nickel oxyhydroxide" refers to any oxyhydroxide containing nickel. The nickel oxyhydroxide may include other cations and anions. A non-limiting example is nickel oxyhydroxide (NiOOH).

[0069] As used herein, "sodium compound" refers to any compound that includes sodium. In one embodiment, the sodium compound includes both sodium and oxygen. Non-limiting examples include NaOH (sodium hydroxide), Na2O (sodium oxide), Na2O2 (sodium peroxide), and Na x NiO2 (sodium nickel oxide), of which 0 <x≤1。

[0070] As used herein, "improvement" with respect to storage stability means that storage stability (i.e., "shelf life") is increased. Generally, an "improvement" in a property or performance indicator of a material or electrochemical cell means that the property or performance indicator is different (compared to a property or performance indicator of a different material or electrochemical cell) in a way that a user or manufacturer of the material or cell would expect (i.e., costs less, lasts longer, provides more power, is more durable, is easier or faster to manufacture, etc.).

[0071] As used herein, "alkali metal" is an element from Group IA of the Periodic Table of Elements. Non-limiting examples include Li, Na, K, Rb, and Cs.

[0072] As used herein, "alkaline earth metals" are elements from Group IIA of the Periodic Table of Elements. Non-limiting examples include Mg, Ca, and Sr.

[0073] As used herein, a "transition metal" is an element from Groups IB-VIIIB of the Periodic Table of the Elements. Non-limiting examples include Co, Mn, Zn, Y, Nb, and Ti.

[0074] As used herein, "other metals" or "another metal" includes all metals on the periodic table not included in the previously mentioned groups, including Al, Ga, In, Sn, Tl, Pb, and Bi.

[0075] As used herein, a "primary" electrochemical cell is a non-rechargeable (ie, disposable) electrochemical cell. A "secondary" electrochemical cell is a rechargeable electrochemical cell.

[0076] As used herein, "electrical conductivity" refers to the ability of a given material to conduct an electric current. This is usually measured in Siemens per meter (S / m).

[0077] As used herein, the terms "pre-aging" or "pre-aged" refer to a controlled process that converts a material over time into a more stable resulting phase or mixture of different phases when used in a final product. For example, a cathode material can be pre-aged using the processes discussed herein to provide a more shelf-stable cathode material when included in a battery. In certain embodiments, the nickelate oxide is pre-aged by exposing the material to a specific concentration of LiOH, NaOH, KOH, and / or other oxides or hydroxides at a specific temperature and for a specified time period. Other hypotheses are that pre-aging can also form a protective film on the high oxidation state surface of the nickel particles to slow down the decomposition reaction from the high nickel oxidation state to the low nickel oxidation state.

[0078] One embodiment is a desodiumed nickelate material, the cathode material having an X-ray diffraction (XRD) pattern, the XRD pattern including a first peak of about 11.9°-14°2θ, a second peak set of about 18°-22°2θ, a third peak of about 36.1°-38.6°2θ, a fourth peak of about 41°-44.2°2θ, a fifth peak of about 55.7°-58.9°2θ, a sixth peak of about 65°-67.3°2θ, and a seventh peak of about 69.5°-71.3°2θ. In an alternative embodiment, the desodiumed nickelate material has an XRD pattern having at least 1, 2, 3, 4, 5, 6, or 7 of these seven peaks or peak sets. In one embodiment, the desodiumed nickelate material has an XRD pattern having a peak of about 69.5°-71.3°2θ.

[0079] One embodiment is a sodium-desorbed nickelate material, the cathode material having an X-ray diffraction (XRD) pattern, the XRD pattern including a first peak of about 11.3°-14.6°2θ, a second peak set of about 17.3°-22.3°2θ, a third peak of about 23.8°-25.9°2θ, a fourth peak of about 27.2°-28.2°2θ, a fifth peak of about 36.2°-37.7°2θ, a sixth peak of about 40°-44°2θ, a seventh peak of about 55.7°-58.5°2θ, an eighth peak of about 65.2°-67.3°2θ, and a ninth peak of about 69.5°-71.1°2θ. In an alternative embodiment, the desodiumated nickelate material has an XRD pattern having at least 1, 2, 3, 4, 5, 6, 7, 8 or 9 of these nine peaks or sets of peaks.

[0080] In one embodiment, the nickelate material has been desodiumized by acid leaching.

[0081] One embodiment is a pre-aged, de-sodiumed nickelate material having an X-ray diffraction (XRD) pattern including a first peak at about 11.9°-13.8°2θ, a second peak at about 17°-19.5°2θ, a third peak at about 24.7°-26.5°2θ, a fourth set of peaks at about 36.3°-39.2°2θ, a fifth set of peaks at about 41.9°-45.7°2θ, a sixth peak at 47.5°-49.5°2θ, a seventh peak at about 50.3°-52°2θ, an eighth peak at about 57.4°-58.7°2θ, and a ninth set of peaks at about 65°-68°2θ. In an alternative embodiment, the desodiumed nickelate material has an XRD pattern having at least 1, 2, 3, 4, 5, 6, 7, 8, or 9 of these nine peaks or sets of peaks. In an embodiment, the desodiumed nickelate material has an XRD pattern having a peak at about 50.3°-52° 2θ.

[0082] One embodiment is a pre-aged, de-sodiumed nickelate material having an X-ray diffraction (XRD) pattern including a first peak at about 11.1°-14.4°2θ, a second set of peaks at about 17.2°-19.9°2θ, a third peak at about 24.1°-26.0°2θ, a fourth set of peaks at about 35.8°-39.3°2θ, a fifth set of peaks at about 43.4°-45.4°2θ, a sixth peak at 47.7°-49.4°2θ, a seventh peak at about 56.8°-59.6°2θ, an eighth peak at about 62.8°-64.5°2θ, a ninth peak at about 65°-67.4°2θ, and a tenth peak at about 68.1°-69.2°2θ. In an alternative embodiment, the desodiumated nickelate material has an XRD pattern having at least 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 of these ten peaks or sets of peaks.

[0083] In one embodiment, the pre-aged de-sodiumed nickelate material has been prepared by pre-aging a de-sodiumed nickelate precursor using a pre-aging solution comprising a hydroxide.

[0084] In one embodiment, the hydroxide is selected from the group consisting of alkali metal hydroxides and alkaline earth metal hydroxides. In one embodiment, the hydroxide is selected from the group consisting of LiOH, NaOH, KOH and Ca(OH)2. In one embodiment, the hydroxide is LiOH or NaOH. In one embodiment, the hydroxide is LiOH. In one embodiment, the hydroxide is NaOH.

[0085] In one example, the pre-aging solution has a hydroxide concentration of about 0.005 M to about 1 M. In one example, the hydroxide concentration is at least, at most, or about 0.005 M, 0.01 M, 0.02 M, 0.05 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M, 0.6 M, 0.7 M, 0.8 M, 0.9 M, or 1.0 M, or within a range bounded by any two of these values.

[0086] In one embodiment, the ratio of the pre-aged solution to the desodiumated nickelate precursor is from about 1 mL / g to about 100 mL / g. In one embodiment, the ratio is at least, at most, or about 1 mL / g, 2 mL / g, 5 mL / g, 10 mL / g, 20 mL / g, 30 mL / g, 40 mL / g, 50 mL / g, 60 mL / g, 70 mL / g, 80 mL / g, 90 mL / g, or 100 mL / g, or within a range bounded by any two of these values.

[0087] In one embodiment, the desodiumed nickelate precursor is pre-aged for about 1-60 minutes. In one embodiment, the desodiumed nickelate precursor is pre-aged for about 1-30 minutes or about 1-20 minutes. In one embodiment, the desodiumed nickelate precursor is pre-aged for at least, at most, or about 1 minute, 2 minutes, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, or 60 minutes, or within a range defined by any two of these values.

[0088] In one embodiment, the pre-aged de-sodiumed nickelate material is pre-aged at a temperature between about 0° C. and about 40° C. In one embodiment, the pre-aged de-sodiumed nickelate material is pre-aged at a temperature of at least, at most, or about 0° C., 5° C., 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., or 40° C., or within a range bounded by any two of these values.

[0089] One embodiment is a method of producing a pre-aged, desodiumated nickelate material, the method comprising:

[0090] i) contacting the sodium nickelate with an acid solution to produce an acid-leached, de-sodiumed nickelate; and

[0091] ii) contacting the acid-leached desodiumated nickelate with a pre-aging solution comprising a hydroxide,

[0092] To produce the pre-aged, desodiumated nickelate material.

[0093] In one embodiment, the acid-leached sodium-free nickelate has the formula Na x NiO2, wherein 0≤x≤0.2. In one embodiment, x is at least, at most, or about 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, or 0.2, or within a range defined by any two of these values.

[0094] In one embodiment, the acid solution comprises an acid selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, hydrobromic acid, hydroiodic acid and perchloric acid. In one embodiment, the acid is sulfuric acid.

[0095] In one embodiment, the acid is present at a concentration of about 0.01 M to about 10 M. In one embodiment, the acid is present at a concentration of at least, at most, or about 1 M, 1.5 M, 2 M, 2.5 M, 3 M, 3.5 M, 4 M, 4.5 M, or 10 M, or within a range bounded by any two of these values.

[0096] In one embodiment, step i) is performed for a time period in the range of about 1 minute to about 60 hours. In one embodiment, the time period is at least, at most, or about 1 minute, 2 minutes, 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, or 50 minutes, or 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 60 hours, or in a range defined by any two of these values.

[0097] In one embodiment, step i) is performed at a temperature of about -5°C to about 20°C. In one embodiment, the temperature is at least, at most, or about -5°C, 0°C, 5°C, 10°C, 15°C, or 20°C, or within a range bounded by any two of these values.

[0098] In one embodiment, step i) is performed using about 10 mL to about 200 mL of acid solution per gram of sodium nickelate. In one embodiment, step i) is performed using at least, at most, or about 10 mL, 20 mL, 30 mL, 40 mL, 50 mL, 60 mL, 70 mL, 80 mL, 90 mL, 100 mL, 110 mL, 120 mL, 130 mL, 140 mL, 150 mL, 160 mL, 170 mL, 180 mL, 190 mL, or 200 mL of acid solution per gram of sodium nickelate, or within a range bounded by any two of these values.

[0099] In one embodiment, the hydroxide is selected from the group consisting of alkali metal hydroxides and alkaline earth metal hydroxides. In one embodiment, the hydroxide is selected from the group consisting of LiOH, NaOH, KOH and Ca(OH)2. In one embodiment, the pre-aging solution includes a hydroxide selected from the group consisting of LiOH, NaOH, Ca(OH)2.

[0100] In one embodiment, the hydroxide is present at a concentration of about 0.005 M to about 1 M. In one embodiment, the hydroxide concentration is at least, at most, or about 0.005 M, 0.01 M, 0.02 M, 0.05 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M, 0.6 M, 0.7 M, 0.8 M, 0.9 M, or 1.0 M, or within a range bounded by any two of these values.

[0101] In one embodiment, step ii) is performed for a time period in the range of about 1-60 minutes. In one embodiment, step ii) is performed for at least, at most, or about 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, or 60 minutes, or within a range defined by any two of these values.

[0102] In one embodiment, step ii) is performed at a temperature of about 0°C to about 40°C. In one embodiment, step ii) is performed at a temperature of at least, at most or about 0°C, 2°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C or 40°C, or within a range bounded by any two of these values.

[0103] One embodiment is a pre-aged, desodiumated nickelate material prepared by any of the methods described herein.

[0104] One embodiment is an alkaline cathode composition comprising any of the pre-aged, desodiumated nickelate materials described herein and electrolytic manganese dioxide (EMD).

[0105] In one embodiment, the ratio of nickel to manganese is 99: 1 to 1: 99 by weight. In one embodiment, the ratio of nickel to manganese is at least, at most, or about 99: 1, 95:5, 90: 10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80, 10:90, 5:95, or 1:99, or within a range bounded by any two of these values.

[0106] One embodiment is an alkaline cathode composition comprising any of the pre-aged, desodiumated nickelate materials described herein, electrolytic manganese dioxide, graphite, and a binder.

[0107] In one embodiment, the pre-aged de-sodiumed nickelate material is present in an amount of about 8.8-45.1 wt.%, electrolytic manganese dioxide is present in an amount of about 48-84.3 wt.%, graphite is present in an amount of about 3-8 wt.%, and the binder is present in an amount of about 0.1-1.0 wt.%, relative to the total weight of the nickelate, EMD, graphite, and binder. In one embodiment, the pre-aged de-sodiumed nickelate material is present in an amount of at least, at most, or about 8.8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, 30 wt.%, 31 wt.%, 32 wt.%, 33 wt.%, 34 wt.%, 35 wt.%, 36 wt.%, 37 wt.%, 38 wt.%, 39 wt.%, 40 wt.%, 41 wt.%, 42 wt.%, 43 wt.%, 44 wt.%, 45 wt.%, 46 wt.%, 47 wt.%, 48 wt.%, 49 wt.%, 50 wt.%, 51 wt.%, 52 wt.%, 53 wt.%, 54 wt.%, 55 wt.%, 56 wt.%, 57 wt.%, 58 wt.%, 59 %, 7wt.%, 28wt.%, 29wt.%, 30wt.%, 31wt.%, 32wt.%, 33wt.%, 34wt.%, 35wt.%, 36wt.%, 37wt.%, 38wt.%, 39wt.%, 40wt.%, 41wt.%, 42wt.%, 43wt.%, 44wt.%, 45wt.% or 45.1wt.%, or in an amount within the range defined by any two of these values. In one embodiment, the electrolytic manganese dioxide is at least, at most, or about 48 wt.%, 49 wt.%, 50 wt.%, 51 wt.%, 52 wt.%, 53 wt.%, 54 wt.%, 55 wt.%, 56 wt.%, 57 wt.%, 58 wt.%, 59 wt.%, 60 wt.%, 61 wt.%, 62 wt.%, 63 wt.%, 64 wt.%, 65 wt.%, 66 wt.%, 67 wt.%, 68 wt.%, 69 wt.%, 70 wt.%, 71 wt.%, 72 wt.%, 73 wt.%, 74 wt.%, 75 wt.%, 76 wt.%, 77 wt.%, 78 wt.%, 79 wt.%, 80 wt.%, 81 wt.%, 82 wt.%, 83 wt.%, 84 wt.%, 85 wt.%, 86 wt.%, 87 wt.%, 88 wt.%, 89 wt.%, 90 wt.%, 91 wt.%, 92 wt.%, 93 wt.%, 94 wt.%, 95 wt.%, 96 wt.%, 97 wt.%, 98 wt.%, 99 wt.%, 100 wt.%, 101 wt.%, 102 wt.%, 103 wt.%, 104 wt.%, 105 wt.%, 106 wt.%, 107 %, 7wt.%, 8 ... In one embodiment, the binder is present in an amount of at least, at most, or about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, or 1.0 wt.%, or within a range defined by any two of these values.

[0108] In one embodiment, the pre-aged de-sodiumed nickelate material and EMD are present together in an amount of about 92-97 wt.%, graphite is present in an amount of about 3-8 wt.%, and the binder is present in an amount of about 0.1-1.0 wt.%. In one embodiment, the pre-aged de-sodiumed nickelate material and EMD are present together in an amount of at least, at most, or about 92 wt.%, 93 wt.%, 94 wt.%, 95 wt.%, 96 wt.%, or 97 wt.%, or in an amount within a range defined by any two of these values. In one embodiment, graphite is present in an amount of at least, at most, or about 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, or 8 wt.%, or in an amount within a range defined by any two of these values. In one embodiment, the binder is present in an amount of at least, at most, or about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, or 1.0 wt.%, or within a range defined by any two of these values.

[0109] One embodiment is a sodium-deionized nickelate material comprising the following phases:

[0110] i) 15-50 wt% NiO2;

[0111] ii) 20-60 wt% of β-NiOOH;

[0112] iii) 0-25 wt% H 0.61 NiO2(H2O) 0.91 ;as well as

[0113] iv) 0-25 wt% Na 0.33 NiO2(H2O) 0.54 .

[0114] In one embodiment, NiO2 is present in an amount of at least, at most, or about 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, 30 wt.%, 31 wt.%, 32 wt.%, 33 wt.%, 34 wt.%, 35 wt.%, 36 wt.%, 37 wt.%, 38 wt.%, 39 wt.%, 40 wt.%, 41 wt.%, 42 wt.%, 43 wt.%, 44 wt.%, 45 wt.%, 46 wt.%, 47 wt.%, 48 wt.%, 49 wt.%, or 50 wt.%, or in an amount within a range defined by any two of these values. In one embodiment, the β-NiOOH is at least, at most, or about 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, 30 wt.%, 31 wt.%, 32 wt.%, 33 wt.%, 34 wt.%, 35 wt.%, 36 wt.%, 37 wt.%, 38 wt.%, 39 wt.%, 40 wt.%, %, 41 wt.%, 42 wt.%, 43 wt.%, 44 wt.%, 45 wt.%, 46 wt.%, 47 wt.%, 48 wt.%, 49 wt.%, 50 wt.%, 51 wt.%, 52 wt.%, 53 wt.%, 54 wt.%, 55 wt.%, 56 wt.%, 57 wt.%, 58 wt.%, 59 wt.% or 60 wt.%, or in an amount within a range defined by any two of these values. In one embodiment, H 0.61 NiO2(H2O) 0.91 In an amount of at least, at most, or about 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, or 25 wt.%, or in a range defined by any two of these values. In one embodiment, H 0.61 NiO2(H2O) 0.91 In one embodiment, Na 0.33 NiO2(H2O) 0.54In an amount of at least, at most, or about 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, or 25 wt.%, or in a range defined by any two of these values. In one embodiment, Na 0.33 NiO2(H2O) 0.54 Does not exist.

[0115] One embodiment is a sodium-deionized nickelate material having the formula Na x NiO2(H2O) z , wherein x = 0.01-0.05, and z = 0.2-1.1. In one embodiment, x is at least, at most, or about 0.01, 0.02, 0.03, 0.04, or 0.05, or within a range defined by any two of these values. In one embodiment, z is at least, at most, or about 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or 1.1, or within a range defined by any two of these values.

[0116] One embodiment is a nickelate material comprising the following phases:

[0117] i) 4-62 wt% Na 0.33 NiO2(H2O) 0.54 ;

[0118] ii) 30-80 wt% (Li 0.39 Ni 0.01 )(NiO2) and / or (Li 0.49 Ni 0.01 )(NiO2) and / or (Li 0.45 Ni 0.05 )(NiO2); and

[0119] iii) 0-50 wt% of β-NiOOH.

[0120] In one embodiment, Na 0.33 NiO2(H2O) 0.54%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4wt.%, 4 %, 35 wt.%, 36 wt.%, 37 wt.%, 38 wt.%, 39 wt.%, 40 wt.%, 41 wt.%, 42 wt.%, 43 wt.%, 44 wt.%, 45 wt.%, 46 wt.%, 47 wt.%, 48 wt.%, 49 wt.%, 50 wt.%, 51 wt.%, 52 wt.%, 53 wt.%, 54 wt.%, 55 wt.%, 56 wt.%, 57 wt.%, 58 wt.%, 59 wt.%, 60 wt.%, 61 wt.% or 62 wt.%, or in an amount within a range defined by any two of these values. In one embodiment, (Li 0.39 Ni 0.01 )(NiO2) and / or (Li 0.49 Ni 0.01 )(NiO2) and / or (Li 0.45 Ni 0.05%), 48 wt.%, 49 wt.%, 50 wt.%, 51 wt.%, 52 wt.%, 53 wt.%, 54 wt.%, 55 wt.%, 56 wt.%, 57 wt.%, 58 wt.%, 59 wt.%, 60 wt.%, 61 wt.%, 62 wt.%, 63 wt.%, 64 wt.%, 65 wt.%, 66 wt.%, 67 wt.%, 68 wt.%, 69 wt.%, 70 wt.%, 71 wt.%, 72 wt.%, 73 wt.%, 74 wt.%, 75 wt.%, 76 wt.%, 77 wt.%, 78 wt.%, 79 wt.%, 80 wt.%, 81 wt.%, 82 wt.%, 83 wt.%, 84 wt.%, 85 wt.%, 86 wt.%, 87 wt.%, 88 wt.%, 89 wt.%, 90 wt.%, %, 56wt.%, 57wt.%, 58wt.%, 59wt.%, 60wt.%, 61wt.%, 62wt.%, 63wt.%, 64wt.%, 65wt.%, 66wt.%, 67wt.%, 68wt.%, 69wt.%, 70wt.%, 71wt.%, 72wt.%, 73wt.%, 74wt.%, 75wt.%, 76wt.%, 77wt.%, 78wt.%, 79wt.% or 80wt.%, or in an amount within the range defined by any two of these values. In one embodiment, the β-NiOOH is at least, at most, or about 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, %. %, 27wt.%, 28wt.%, 29wt.%, 30wt.%, 31wt.%, 32wt.%, 33wt.%, 34wt.%, 35wt.%, 36wt.%, 37wt.%, 38wt.%, 39wt.%, 40wt.%, 41wt.%, 42wt.%, 43wt.%, 44wt.%, 45wt.%, 46wt.%, 47wt.%, 48wt.%, 49wt.% or 50wt.%, or in an amount within a range defined by any two of these values. In one embodiment, β-NiOOH is absent.

[0121] One embodiment is a nickelate material comprising the following phases:

[0122] i) 80-85 wt% Na 0.33 NiO2(H2O) 0.54 ;as well as

[0123] ii) 15-20 wt% of β-NiOOH.

[0124] In one embodiment, Na0.33 NiO2(H2O) 0.54 In an amount of at least, up to or about 80 wt.%, 81 wt.%, 82 wt.%, 83 wt.%, 84 wt.% or 85 wt.%, or in a range defined by any two of these values. In one embodiment, β-NiOOH is present in an amount of at least, up to or about 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.% or 20 wt.%, or in a range defined by any two of these values.

[0125] One embodiment is a nickelate material having the formula Na x Li y NiO2(H2O) z , wherein x = 0.01-0.05, y = 0.15-0.45, and z = 0.1-0.8. In one embodiment, x is at least, at most, or about 0.01, 0.02, 0.03, 0.04, or 0.05, or within a range defined by any two of these values. In one embodiment, y is at least, at most, or about 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, or 0.45, or within a range defined by any two of these values. In one embodiment, z is at least, at most, or about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, or 0.8, or within a range defined by any two of these values.

[0126] One embodiment is a nickelate material that exhibits three discharge plateaus relative to a Zn / ZnO reference electrode during discharge at a discharge rate of 10 mA / g to a voltage of 1.0 V.

[0127] In one embodiment, the nickelate material exhibits a discharge plateau of about 1.85-1.80 V during discharge at a discharge rate of 10 mA / g.

[0128] In one embodiment, the nickelate material exhibits a discharge curve relative to Zn / ZnO at a discharge rate of 10 mA / g, wherein the discharge curve depicts voltage relative to specific capacity; wherein the specific capacity is divided into a first region of OCV to 1.63V; a second region of 1.63V to 1.45V; and a third region of 1.45V to 1.00V; wherein the capacity contribution of a given region is the difference between the capacity at the end of the region and the capacity at the beginning of the region; and

[0129] i) a ratio of the capacity contribution of the second region to the capacity contribution of the first region is less than 10; or

[0130] ii) the capacity contribution of the first zone relative to the total capacity contribution of the first zone, the second zone and the third zone is at least 7.0%.

[0131] In one embodiment, the ratio of the capacity contribution of the second zone to the capacity contribution of the first zone is less than 9, 8, 7, 6, 5, 4, 3, 2 or 1. In one embodiment, the capacity contribution of the first zone is at least 7.0%, 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 18.0%, 19.0% or 20.0% relative to the total capacity contribution of the first zone, the second zone and the third zone.

[0132] One embodiment is a composition comprising particles comprised of a nickelate material, wherein the particles comprise:

[0133] i) an inner core comprising a nickelate that has not been pre-aged with a hydroxide; and

[0134] ii) an outer layer comprising a nickelate that has been pre-aged with a hydroxide.

[0135] The pre-aged nickelate may be any of the pre-aged desodiumed nickelates described herein. In one embodiment, the inner core comprises a desodiumed nickelate as described herein.

[0136] In one embodiment, the thickness of the outer layer is 0.1% to 99% of the particle radius. In one embodiment, the radius of the inner core is 1% to 99.9% of the particle radius. Fig. 22 , in which the inner core is shaded; the radius of the particle is labeled "p", the radius of the inner core is labeled "i", and the thickness of the outer layer is labeled "e". The particle radius can be defined as the sum of the radius inner core and the thickness of the outer layer (p=i+e).

[0137] One embodiment is an alkaline electrochemical cell comprising any of the nickelate materials or compositions described herein.

[0138] refer to Figure 1 The embodiments will be better understood with the figures showing a cylindrical battery cell 1 in elevation cross section, wherein the battery cell has a nail-type or spool-type configuration and is sized comparable to a conventional LR6 (AA) sized alkaline battery cell, which is particularly suitable for these embodiments. However, it should be understood that the battery cells according to these embodiments may have other sizes and shapes (such as a prismatic shape or a button-type shape) and other electrode configurations as known in the art. Figure 1The materials and designs of the components of the electrochemical cell shown in the drawings are for illustration purposes only, and other materials and designs may be substituted. In addition, in certain embodiments, the cathode material and the anode material may be coated onto the surface of the separator and / or the current collector and may be rolled to form a "jelly roll" configuration.

[0139] exist Figure 1 In the embodiment, an electrochemical cell 1 is shown, which includes a container or can 10 having a closed bottom end 24, a top end 22, and a side wall 26 located therebetween. The closed bottom end 24 includes a terminal cover 20, which includes a protrusion. The can 10 has an inner wall 16. In the embodiment, the positive terminal cover 20 is welded or otherwise attached to the bottom end 24. In one embodiment, the terminal cover 20 can be formed of electroplated steel (e.g., electroplated steel with a small piece protruding at its central area). The container 10 can be formed of a metal such as steel, preferably electroplated with nickel, cobalt and / or other metals or alloys or other materials having sufficient structural properties compatible with various inputs in the electrochemical cell. The label 28 can be formed around the outer surface of the container 10 and can be formed on the outer peripheral edges of the positive terminal cover 20 and the negative terminal cover 46, as long as the negative terminal cover 46 is electrically insulated from the container 10 and the positive terminal 20.

[0140] Disposed within the container 10 are the first electrode 18 and the second electrode 12 and the separator 14 therebetween. The first electrode 18 is disposed within a space defined by the separator 14 and a closure assembly 40 secured to the open end 22 of the container 10. The closed end 24, the sidewall 26, and the closure assembly 40 define a cavity in which the electrodes of the battery cell are housed.

[0141] The closed assembly 40 includes a closed member 42 such as a gasket, a current collector 44, and a conductive terminal 46 in electrical contact with the current collector 44. The closed member 42 preferably contains a pressure relief port that will allow the closed member to rupture when the internal pressure of the battery cell becomes excessive. The closed member 42 can be formed of a polymer or elastomeric material (e.g., nylon-6,6), an injection moldable polymer blend (e.g., a polypropylene matrix combined with poly(phenylene oxide) or polystyrene), or another material (e.g., a metal), provided that the current collector 44 and the conductive terminal 46 are electrically insulated from the container 10 that serves as the current collector of the second electrode 12. In the embodiment shown, the current collector 44 is an elongated nail or spool-shaped component. The current collector 44 is made of a metal or metal alloy (e.g., copper or brass), a conductively plated metal or plastic current collector, etc. Other suitable materials can be used. The current collector 44 is inserted through a preferably centrally located hole in the closed member 42.

[0142] The first electrode 18 is preferably a negative electrode or anode. The negative electrode comprises a mixture of one or more active materials, a conductive material, solid zinc oxide, and a surfactant. The negative electrode may optionally contain other additives, such as a binder or a gelling agent, etc.

[0143] Zinc is an example primary active material for the negative electrode of the described embodiments. Mercury and magnesium may also be used. Preferably, the volume of active material used in the negative electrode is sufficient to maintain the desired particle-to-particle contact and the desired anode to cathode (A:C) ratio.

[0144] Particle-to-particle contact should be maintained during the useful life of the battery. If the volume of active material in the negative electrode is too low, the voltage of the cell may suddenly drop to an unacceptably low value when the cell is powered to a device. It is believed that the voltage drop is caused by the loss of continuity of the conductive matrix of the negative electrode. The conductive matrix can be formed by undischarged active material particles, conductive electrochemically formed oxides, or a combination thereof. The voltage drop may occur after the oxide begins to form, but before a sufficient network is established to bridge all active material particles present.

[0145] The alkaline electrolyte aqueous solution may include an alkaline metal hydroxide, such as potassium hydroxide (KOH), sodium hydroxide (NaOH), etc., or a mixture thereof. Potassium hydroxide is preferred. The alkaline electrolyte used to form the gelled electrolyte of the negative electrode contains an alkaline metal hydroxide in an amount of about 26 wt % to about 36 wt % (e.g., about 26 wt % to about 32 wt %, and specifically, about 26 wt % to about 30 wt %) based on the total weight of the alkaline electrolyte. There is an interaction between the negative electrode alkali metal hydroxide and the added solid zinc oxide, and it is found that lower alkali metal hydroxides improve DSC service. Electrolytes with lower alkalinity are preferred, but they may result in rapid electrolyte separation of the anode. An increase in the concentration of alkali metal hydroxides produces a more stable anode, but may reduce DSC service.

[0146] A gelling agent well known in the art is preferably utilized in the negative electrode, such as a cross-linked polyacrylic acid, such as that available from Noveon, Inc. of Cleveland, Ohio, USA. 940. Carboxymethyl cellulose, polyacrylamide and sodium polyacrylate are examples of other gelling agents suitable for alkaline electrolyte solutions. In order to maintain a substantially uniform dispersion of zinc and solid zinc oxide particles in the negative electrode, a gelling agent is desirable. The amount of gelling agent present is selected so that a low electrolyte separation rate is obtained and the anode viscosity at yield stress is not too large, which may cause anode dispersion problems.

[0147] Other components that may optionally be present in the negative electrode include, but are not limited to, gassing inhibitors, organic or inorganic corrosion inhibitors, plating agents, binders, or other surfactants. Examples of gassing inhibitors or corrosion inhibitors may include indium salts (such as indium hydroxide), perfluoroalkyl ammonium salts, alkali metal sulfides, and the like. In one embodiment, dissolved zinc oxide is preferably present by dissolving in the electrolyte to improve electroplating on a bobbin or nail-type current collector and reduce negative electrode shelf gassing. The added dissolved zinc oxide is separate and different from the solid zinc oxide present in the anode composition. In one embodiment, a level of dissolved zinc oxide in an amount of about 1% by weight based on the total weight of the negative electrode electrolyte is preferred. The BET surface area of ​​soluble or dissolved zinc oxide measured using a Tristar 3000 BET specific surface area analyzer from Micrometrics (the analyzer has a multi-point calibration after zinc oxide is degassed at 150°C for one hour) is generally about 4 m 2 / g or less; and the particle size D50 (median diameter) measured using the CILAS particle size analyzer as indicated above is generally about 1 micron. In a further embodiment, in the negative electrode, in order to substantially prevent the battery cell from shorting through the separator during discharge of the battery cell, an amount of about 0.3 wt % sodium silicate based on the total weight of the negative electrode electrolyte is preferred.

[0148] The negative electrode can be formed in a variety of different ways known in the art. For example, the negative electrode components can be dry blended and added to the battery cell, with the alkaline electrolyte added separately, or as in a preferred embodiment, using a pre-gelled negative electrode process.

[0149] The second electrode 12 (also referred to herein as the positive electrode or cathode) has a nickelate compound (or "nickelate cathode material") as its electrochemically active material. The active material is present in an amount of generally about 80 wt% to about 98 wt%, and preferably about 81 wt% to 97 wt%, based on the total weight of the positive electrode (i.e., nickelate cathode material, binder, conductive material, positive electrode electrolyte, and additives (if present)).

[0150] The active cathode material can be a blend of nickelate cathode material with other active materials such as electrolytic manganese dioxide (EMD), chemical manganese dioxide (CMD), copper oxide, etc. The weight % of the nickel-containing compound can range from 5% to 100% of the total active cathode material. The positive electrode is formed by combining and mixing the desired components of the electrode, followed by dispersing a certain amount of the mixture into the open end of the container, and then using a punch to mold the mixture into a solid tubular configuration, the solid tubular configuration defining a cavity within the container, and the diaphragm 14 and the first electrode 18 are then placed in the cavity (referred to as impact molding). Figure 1As shown, the second electrode 12 has a ledge 30 and an inner surface 32. Alternatively, the positive electrode may be formed by preforming a plurality of rings from a mixture comprising the nickelate cathode material and then inserting the rings into a container to form a tubular shaped second electrode (referred to as ring molding). Figure 1 The cell shown would typically contain 3 or 4 rings.

[0151] The active material can be in the form of particles of any size suitable for use in an electrode mixture. In one embodiment, the active material is in the form of particles having an average size of about 1-20 microns, or 1-10 microns, or 1-5 microns, or 7-10 microns. In one embodiment, the active material is in the form of particles having a size in the range of 0.1-40 microns.

[0152] The cathode also includes a binder, which can be any binder known in the art. Non-limiting examples of binders include polyvinylidene fluoride (PVDF), polyethylene, polystyrene- and ethylene / propylene-based copolymers (such as those sold by Kraton Corporation (Houston, TX)), and polyvinylidene fluoride (PVDF). The binder may be in the form of particles of any size suitable for use in an electrode mixture.

[0153] The cathode also includes a conductive material, which can be conductive carbon. The conductive carbon can be graphite, and the graphite can be expanded graphite. The graphite can be in the form of particles of any size suitable for the electrode mixture. In one embodiment, the graphite is in the form of particles with an average size ranging from nanoparticle size to 65 microns. In one embodiment, the maximum size of the graphite particles is 110 microns.

[0154] An example of another cathode additive is barium sulfate (BaSO4), which is commercially available from Bario E. Derivati ​​SpA of Massa, Italy. Barium sulfate is present in an amount generally from about 1 wt% to about 2 wt%, based on the total weight of the positive electrode. Other additives may include, for example, barium acetate, titanium dioxide, a binder (such as (Axalta Coating Systems, Glen Mills, PA) and calcium stearate.

[0155] One of the parameters used by cell designers characterizes the cell design as the ratio of the electrochemical capacity of one electrode to the electrochemical capacity of the opposite electrode, such as the ratio of the anode (A) to the cathode (C), i.e., the A:C ratio. For an LR6-type alkaline primary cell utilizing zinc in the negative electrode or anode and MnO2 in the positive electrode or cathode, the A:C ratio may be greater than 1.1:1, such as greater than 1.2:1, and specifically, 1.3:1 for an impact molded positive electrode. The A:C ratio of a ring molded positive electrode may be from about 1.3:1 to about 1.1:1.

[0156] A separator 14 is provided to separate the first electrode 18 from the second electrode 12. The separator 14 maintains the physical dielectric separation of the electrochemically active material of the positive electrode from the electrochemically active material of the negative electrode and allows ions to be transported between the electrode materials. In addition, the separator acts as a wicking medium for the electrolyte and a sleeve that prevents the fragmented portion of the negative electrode from contacting the top of the positive electrode. The separator 14 can be a layered ion-permeable nonwoven fiber fabric. Typical separators typically contain two or more layers of paper. Conventional separators are typically formed by preforming the separator material into a cup-shaped basket, which is then inserted under the cavity defined by the second electrode 12 and the closed end 24 and any positive electrode material located on the closed end; or during battery cell assembly, two rectangular separators are inserted into the cavity to form a basket with the materials rotated 90° relative to each other. Conventional preformed separators are typically made of a piece of nonwoven fabric that is rolled into a cylindrical shape that conforms to the inner wall of the second electrode and has a closed bottom end.

[0157] All references cited above and all references cited herein are incorporated by reference in their entirety.

[0158] Although the embodiments have been shown and described in detail above, such illustrations and descriptions are to be regarded as illustrative or exemplary, rather than restrictive. It will be understood that changes and modifications may be made by those of ordinary skill in the art within the scope and spirit of the following claims. Specifically, the embodiments include any combination of features from the different embodiments described above and below.

[0159] The embodiments are further described by way of the following illustrative non-limiting examples that provide a better understanding of the embodiments and their many advantages. The following examples are included to illustrate the preferred embodiments. It should be understood by those skilled in the art that the techniques disclosed in the following examples represent the techniques used in the embodiments to work well in the practice of the embodiments and therefore can be considered to constitute the preferred mode of their practice. However, in light of the present disclosure, it should be understood by those skilled in the art that many changes may be made to the specific embodiments disclosed and still similar or similar results may be obtained without departing from the spirit and scope of the embodiments.

[0160] Discussion and Examples

[0161] Example 1: NaNiO2 synthesis

[0162] Ni(OH)2 was calcined at 650°C in air for 6 hours to convert it to NiO. The resulting NiO and Na2O2 purchased from Sigma-Aldrich were added to a ball milling vial to form a mixture with a Na / Ni molar ratio of 1.35. The vial was filled with argon in a glove box, and the precursors were thoroughly mixed for 1 hour by high-energy ball milling. The ball-milled mixture was then collected in a nickel crucible and covered, and then calcined at 680°C in air in a furnace for 30 hours. The temperature ramp and cooling rates were 5°C / min and 1°C / min, respectively. The powder XRD pattern of the synthesized material was analyzed with an X-ray diffractometer, and the phase identified was NaNiO2, such as Figure 2 shown.

[0163] Example 2: Sodium removal by acid leaching

[0164] To remove sodium by acid leaching, NaNiO2 synthesized by Example 1 is added to the bottom of a round-bottomed flask. The flask is immersed in a beaker filled with water from an ice / water mixture. The starting temperature of the water in the beaker is about 2°C. 4MH2SO4 (10 mL acid per gram of powder) is cooled to about -5°C to -2°C in a freezer, after which the solution is heated to a temperature of 0°C and added to the powder. The first half of the acid is added in about 1-3 minutes with a disposable transfer pipette. After half of the acid has been added, the remaining acid is poured into the flask. Then, the beaker / flask setup is transferred to a refrigerator controlled at 2°C and stirred for 4 hours. The final temperature of the water bath is about 5°C to 6°C. Finally, the contents of the round-bottomed flask are poured into a filtration setup to filter and wash the powder until the pH of the filtrate matches the pH of the DI water. The powder was dried under vacuum at 60°C for 18 hours and then kept in vacuum for another 24 hours after the heat was turned off. The dried powder was identified by XRD as primarily nickel oxide (NiO2, PDF 04-010-4751), as Figure 3shown.

[0165] Example 3: Aged raw powder in 40wt% KOH / 6wt% ZnO for 24 hours

[0166] 0.12 g of the original powder was mixed with 0.6 g of 40 wt% KOH / 6 wt% ZnO in a small beaker and the solution was stirred continuously for 24 hours at room temperature. The contents of the beaker were poured into a filtration setup to filter and wash the powder until the pH of the filtrate matched that of DI water. The powder was dried under vacuum at 60 °C for 18 hours. The dried material was identified as primarily Na 0.33 NiO2(H2O) 0.5 (PDF 04-015-9998), such as Figure 4 shown.

[0167] Example 4: LiOH Pre-Aging of Nickel Oxide from Example 2

[0168] 0.45 g of the powder from Example 2 was placed into a centrifuge tube and 30 mL of lithium hydroxide (LiOH) solution was added to the centrifuge tube to pre-age the material. The tube was shaken in a circular motion to disperse the agglomerates at the bottom and then allowed to settle and stand for 10 minutes. After the pre-aging was complete, the sample was then washed with DI water by a vacuum filtration setup until the pH of the filtrate matched that of the DI water. The powder was then dried at 60°C under a vacuum of -1 bar for 18 hours and the drying was extended for another 24 hours after the heat was turned off. XRD showed that the resulting material included Na 0.33 NiO(H2O) 0.5 (PDF 04-015-9998) and (Li 0.45 Ni 0.05 )(NiO2)(PDF 01-085-1983), such as Figure 5 Two different concentrations of LiOH (0.1 M and 0.5 M) were evaluated and it was found that the sample pre-aged at the higher LiOH concentration (0.5 M) showed (Li 0.45 Ni 0.05 The peak of )(NiO2) is stronger than that of the sample aged at low LiOH concentration (0.1 M).

[0169] Example 5: Pre-aged powder aged in 40wt% KOH / 6wt% ZnO for 24 hours

[0170] 0.5 g of the pre-aged powder from Example 4 was aged in 40 wt% KOH / 6 wt% ZnO according to the same conditions and procedures as in Example 3. The resulting material included the same phases as those of the material in Example 4.0.33 NiO(H2O) 0.5 (PDF 04-015-9998) and (Li 0.45 Ni 0.05 )(NiO2)(PDF 01-085-1983). However, after aging in KOH solution, Na 0.33 NiO(H2O) 0.5 The intensity of the peaks increases significantly, such as Figure 6 shown.

[0171] Example 6: Pre-Aging Improves Stability of EMD / Nickelate Mixtures

[0172] After the cells were aged at 60°C for up to 14 days, the nickelate / EMD mixtures were discharged in a half-cell test apparatus to determine the electrochemical discharge capacity retention as follows: First, EMD (50 wt% Mn relative to the total weight of Ni and Mn) was mixed with 6.4 wt% SFG 15 graphite and 0.5 wt% coathylene binder, and then nickelate (50 wt% Ni relative to the total weight of Ni and Mn) without pre-aging or nickelate pre-aged with 0.1 M LiOH for 1 minute was added to form a cathode. The total weight percentage of EMD and nickelate relative to the total cathode weight was 93.1 wt%. For reference, 93.1 wt% EMD relative to the total cathode weight (100 wt% Mn relative to the total Ni and Mn) was also mixed with 6.4 wt% SFG15 graphite and 0.5 wt% coathylene binder to form a cathode. 200 mg of cathode was pressed into a 357 coin cell can with a force of 5,000 lbf. The coin cell was placed in an acrylic plastic test fixture filled with 40 wt% KOH and 6 wt% ZnO electrolyte. The acrylic plastic test fixture containing the nickelate / EMD mixture cathode was aged in a 60°C oven for 3 days, 7 days, and 14 days. Afterwards, the acrylic plastic test fixture was removed from the oven and cooled at room temperature for 1 hour, then the electrolyte was poured out and the acrylic plastic test fixture was refilled with 15 g of fresh electrolyte. The acrylic plastic test fixture was discharged at a rate of 10 mA / g, with a 1 hour rest for every 5 hours of discharge to observe voltage recovery. Figure 7A comparison of the specific capacities at 1 V of EMD, nickelates without pre-aging, and nickelates pre-aged with LiOH after aging of half-cells at 60° C. for up to 14 days is presented. It can be observed that the nickelate pre-aged for 1 minute in 0.1 M LiOH (LPA-50% Ni) shows the highest fresh capacity of 292 mAh / g compared to nickelates without pre-aging (NPA-50% Ni, 244 mAh / g) and EMD (268 mAh / g). After aging of the half-cell at 60° C. for 14 days, LPA-50% Ni still maintains a capacity of 268 mAh / g, which is higher than that of NPA-50% Ni (214 mAh / g) and EMD (257 mAh / g), indicating that the stability of the EMD / nickelate mixture is improved due to the pre-aging treatment.

[0173] Example 7: Pre-aging improves the stability of nickelate powders

[0174] Powder aging tests were completed for both the nickelates without pre-aging and the nickelates with pre-aging. The procedure for the powder aging test was as follows. First, 0.12 g of the original powder was mixed with 0.6 g of 40 wt% KOH / 6 wt% ZnO in a small vial at room temperature and stirred for 24 hours. The mixture was then washed with DI water using a filtration setup until the pH of the washed product was close to 7. The final product was obtained after the powder was dried at 60°C under vacuum for 18 hours and dried for another 24 hours after turning off the heat. The original powder was then discharged in a half-cell test device before and after aging for 24 hours to determine the electrochemical discharge capacity as follows: 49 wt% of the active material was mixed with 49 wt% of SFG 15 graphite and 2 wt% of coathylene binder to form a cathode mixture. 200 mg of the cathode mixture was pressed into a 357 button cell can with a force of 5,000 lbf. The button cell was placed into an acrylic plastic test fixture filled with 40 wt % KOH and 6 wt % ZnO; and the button cell was discharged at a rate of 10 mA / g, with a 1 hour rest period after every 5 hours of discharge to observe voltage recovery. Figure 8 The discharge curves of nickelates without pre-aging and nickelates with LiOH pre-aging before and after aging for 24 hours in 40wt% KOH / 6wt% ZnO are shown. Although the nickelates without pre-aging showed the highest initial capacity of 424 mAh / g at 1V, its capacity was only 230 mAh / g after powder aging. In contrast, nickelates with LiOH pre-aging at different concentrations showed much higher capacities of 305-311 mAh / g after powder aging (Table 1), indicating that the stability of nickelates was improved by the pre-aging treatment technique.

[0175] Table 1: Comparison of initial OCV and capacity of nickelates without pre-aging and nickelates pre-aged with LiOH after aging for 24 h in 40 wt % KOH / 6 wt % ZnO.

[0176]

[0177] Example 8: Optimization of EMD / Pre-Aged Nickelate Mixtures

[0178] The nickelate / EMD mixture pre-aged with 0.1M LiOH was discharged in a half-cell test apparatus to determine the electrochemical discharge capacity and efficiency as follows: The nickelate and EMD pre-aged with 0.1M LiOH were mixed in a certain ratio (93.1wt% total nickelate and EMD relative to the total cathode weight) with 6.4wt% SFG 15 graphite and 0.5wt% coathylene binder to form a cathode mixture. 200mg of the cathode mixture was pressed into a 357 button cell can with a force of 5,000lbf. The button cell was placed in an acrylic plastic test fixture filled with 40wt% KOH and 6wt% ZnO; and the button cell was discharged at a rate of 10mA / g, with a rest of 1 hour every 5 hours of discharge to observe voltage recovery. Fig. 9 and 10 The specific capacity and efficiency of the nickelate / EMD mixture pre-aged with 0.1M LiOH at 1V with different wt% relative Ni were compared. It can be observed that the nickelate / EMD mixture pre-aged with 0.1M LiOH having a relative nickel content of 50wt% (meaning 50wt% Ni relative to the total amount of nickel and manganese) exhibited the highest capacity at 1V compared to the nickelate / EMD mixture without pre-aging. In particular, the efficiency of the nickelate / EMD mixture pre-aged with 0.1M LiOH was greatly improved ( Fig.10 ). Overall, 50 wt% relative Ni is the optimal Ni content for the nickelate / EMD mixture pre-aged with 0.1 M LiOH, which shows good capacity (305 mAh / g) and high efficiency (96%) at 1 V.

[0179] Example 9: XRD fingerprints before and after LiOH pre-aging

[0180] Table 2 below depicts the sodium-depleted NaNiO2 (acid-treated, without pre-aging, Figure 3 ) and LiOH pre-aged nickelates (acid treated, pre-aged, Figure 5 ) together with the XRD peak positions (2θ) of another nickelate material described in U.S. Patent No. 11,560,321 B2.

[0181] Table 2

[0182]

[0183]

[0184] For the de-sodiumed NaNiO2 without pre-aging ( Figure 3 ), it can be observed that the fifth peak at about 55.7-58.9 2θ and the seventh peak at 69.5-71.3 2θ correspond to the NiO2 phase, which is different from any peak in patent US11,560,321B2. Figure 5 ), it can be observed that the seventh peak at about 50.3-52 2θ and the eighth peak at 57.4-58.7 2θ correspond to Na 0.33 NiO2(H2O) 0.54 Phase and (Li 0.45 Ni 0.05 )(NiO2) phase, which is different from any peak of the material described in US 11,560,321 B2.

[0185] Table 3 below contains the peak positions (2θ) described in Table 2, along with additional XRD peaks from non-pre-aged nickelates and LiOH pre-aged nickelates from alternative synthetic routes.

[0186] Table 3

[0187]

[0188] For scale-up purposes, the alternative synthetic routes for nickelates without pre-aging and nickelates pre-aged with LiOH (described in Examples 10-12) were slightly modified and showed distinct XRD fingerprints, such as Fig.11 and 12 What you see.

[0189] Peak splitting phenomenon

[0190] For the nickelate without pre-aging, the main XRD peak at about 17.3-22.3 2θ has peak splitting ( Fig.11 ), which is not observed in α-nickelate, β-nickelate and sodium nickelate in US 11,560,321 B2 ( Fig.13 ). The main peak can be subdivided into three peaks with different intensity ratios, and the three peaks correspond to H 0.61 NiO2(H2O) 0.91 phase, β-NiOOH phase and NiO2 phase.

[0191] For the nickelate pre-aged with LiOH, there is a peak splitting of the second peak at about 17.2-19.9 2θ, the fourth peak at about 36.4-37.8 2θ, and the fifth peak at about 43.4-45.4 2θ ( Fig.12 ), which is not observed in α-nickelates, β-nickelates, and X-nickelates ( Fig.13 This is due to the presence of multiple phases in the LiOH-pre-aged nickelates, such as the β-NiOOH component, Na 0.33 NiO2(H2O) 0.54 Components and (Li 0.39 Ni 0.01 )(NiO2) component.

[0192] Unique XRD peaks

[0193] For the nickelate without pre-aging, it can be observed that the fourth peak at about 27.2-28.2 2θ, the seventh peak at 55.7-58.5 2θ and the ninth peak at 69.5-71.1 2θ (Table 3) are different from any peaks in patent US 11,560,321 B2.

[0194] For the LiOH pre-aged nickelate, it can be observed that the fifth peak at about 43.4-45.4 2θ, the seventh peak at 56.8-59.6 2θ and the tenth peak at 68.1-69.2 2θ (Table 3) are different from any peaks in patent US 11,560,321 B2.

[0195] Example 10: Synthesis of Nickelate I without Pre-Aging

[0196] Ni(OH)2 was calcined at 650°C in air for 6 hours to be converted into NiO. 8.963g of NiO and 6.319g of Na2O2 purchased from Sigma Aldrich were added to a ball milling vial to form a mixture. Then, the ball milling vial was purged with argon in a glove box, followed by mixing by high-energy ball milling for 1 hour. Then, the ball-milled mixture was collected on a nickel crucible (55mL) and covered with a lid, followed by calcination at 680°C in air in a furnace for 30 hours. The temperature ramp and cooling rate were 5°C / min and 1°C / min, respectively. After the powder was taken out of the furnace at 120°C, 13g of powder was added to the bottom of a round-bottomed flask, which was then immersed in a beaker filled with water from an ice / water mixture. Then 4M sulfuric acid (the ratio of sample mass to volume was 1:10g / mL) at a temperature of 0°C was added to the flask and stirred in a refrigerator (2°C) for 4 hours. After that, the sample was first washed by centrifugation (1500 / 2000 rpm, 1-2 minutes, 0-4°C) to remove the acid. Subsequently, the sample was washed by DI water through a filtration setting. After the washed sample was dried under vacuum for 10 minutes, then continuously heated at 60°C for 18 hours, and cooled for about 22-24 hours, the final product, nickelate I, was obtained without pre-aging. Fig.11 Shows the XRD pattern of the synthesized nickelate I without pre-aging.

[0197] Example 11: Synthesis of Nickelate II without Pre-Aging

[0198] Ni (OH) 2 is calcined at 650 ℃ in air for 6 hours to be converted into NiO. 11.204g of NiO obtained and 7.895g of Na 2 O 2 purchased from Sigma Aldrich are added to two ball milling vials separately to form a mixture. Then, the ball milling vials are purged with argon in a glove box, and then mixed by high-energy ball milling for 1 hour. Then, the ball-milled mixture is collected on a nickel crucible (250mL) and covered with a lid, and then calcined at 680 ℃ in air in a furnace for 30 hours. The temperature ramp and cooling rate are 5 ℃ / minute and 1 ℃ / minute respectively. After the powder is taken out from the furnace at 130 ℃, separately, 34g of powder is added to the bottom of two round-bottomed flasks, and then the round-bottomed flasks are immersed in a beaker filled with water from an ice / water mixture. Then 4M sulfuric acid (sample mass to volume ratio of 1:10 g / mL) at 0°C was added to each flask and stirred in a refrigerator (2°C) for 4 hours. The samples were then washed with DI water by vacuum filtration using a large ceramic filter cup. After the washed samples were dried under vacuum for 10 minutes, then heated continuously at 60°C for 18 hours, and cooled for about 22-24 hours, the final product, nickelate II, was obtained without pre-aging. Fig.11Shows the XRD pattern of the synthesized nickelate II without pre-aging.

[0199] Example 12: Synthesis of LiOH-pre-aged nickelates I / II

[0200] First, 40 mL of 0.1 M LiOH solution was added to a centrifuge tube containing 0.6 g of nickelate I / II powder without pre-aging. After shaking the tube in a circular motion, the tube was allowed to stand at room temperature for about 1 minute to pre-age the material. The sample was then washed with DI water using a vacuum filtration setup and dried in a vacuum oven at 60° C. for 18 hours. The final product, nickelate I / II pre-aged with LiOH, was obtained. Fig.12 The XRD pattern of the synthesized LiOH pre-aged nickelate I / II is shown. The LiOH pre-aged nickelate was also prepared by a similar method, but using 0.5 M LiOH.

[0201] Example 13: Sodium Nickelate Compositions Before and After LiOH Pre-Aging

[0202] Rietveld refinement of the XRD pattern enables quantification of the weight percentages of the different compounds that make up the nickelate without pre-aging and the pre-aging. It was found that the de-sodiumed NaNiO2 consists of 2 to 4 phases, namely 18 wt% to 50 wt% NiO2 (PDF: 04-010-4751), 20-60 wt% β-NiOOH (ICSD: 165961), 0-25 wt% Na 0.33 NiO2(H2O) 0.54 (ICSD: 159386) and 0wt% to 22wt% H 0.61 NiO2(H2O) 0.91 After pre-aging in LiOH, it was found that the pre-aged nickelate includes 2 to 3 phases, namely 0 wt% to 50 wt% of β-NiOOH (ICSD 165961), 4 wt% to 62 wt% of Na 0.33 NiO2(H2O) 0.54 (ICSD: 159386) and 35wt% to 80wt% (Li 0.39 Ni 0.01 )(NiO2)(ICSD:78694) or (Li 0.49 Ni 0.01 )(NiO2)(ICSD:78693) or (Li 0.45 Ni 0.05After pre-aging in NaOH, it was found that the pre-aged nickelate contained 15-20 wt% β-NiOOH (ICSD 165961) and 80-85 wt% Na 0.33 NiO2(H2O) 0.54 (ICSD: 159386).

[0203] ICP analysis made it possible to determine the chemical formula of the nickelate thus prepared to follow the Na x Li y NiO2(H2O) z The general format of , where before pre-aging, x = 0.01-0.05 and z = 0.2-1.1, and after pre-aging in LiOH, x = 0.01-0.05, y = 0.15-0.4, and z = 0.1-0.8.

[0204] A quantitative summary of the XRD phase composition and overall chemical composition of the non-pre-aged and pre-aged nickelates is shown in Table 4 below:

[0205] Table 4

[0206]

[0207] The Rietveld refinement of the XRD patterns of nickelate I without pre-aging and nickelate II without pre-aging is Figure 14-15 Found in.

[0208] The Rietveld refinement of the XRD patterns of pre-aged nickelate I (0.1 M LiOH, 1 min) and pre-aged nickelate II (0.1 M LiOH, 1 min) are respectively Figure 16-17 Found in.

[0209] The Rietveld refinement of the XRD patterns of the pre-aged nickelate (0.5 M LiOH, 10 min) and the pre-aged nickelate (0.1 M LiOH, 10 min) prepared according to Example 4 are respectively Figure 18-19 Found in.

[0210] Example 14: Discharge curve characteristics of NaNiO2-derived nickelates compared to LiNiO2-derived nickelates based on a 10 mA / g discharge rate

[0211] Unlike the discharge curves of α-nickelates and β-nickelates derived from LiNiO2, the discharge curves of desodiumed NaNiO2 before and after pre-aging in LiOH solution include three different discharge plateaus during discharge to a voltage of 1.0V at a discharge rate of 10 mA / g. In addition to the discharge plateaus observed at about 1.60-1.50 V and 1.45-1.35 V, there is an additional unique discharge plateau at about 1.85-1.80 V for desodiumed NaNiO2 before and after LiOH pre-aging, which is not observed in α-nickelates and β-nickelates. This unique discharge plateau at a higher voltage of 1.85-1.80 V may be inherent to nickelates derived from acid treatment of sodium nickelate rather than lithium nickelate. This is shown in Fig. 20 middle.

[0212] Example 15: Ratio of Capacity Contributions from Different Regions of the Discharge Curve

[0213] Relatedly, the specific capacity distributions of the nickelates without pre-aging (de-sodiumized NaNiO2) and the subsequent LiOH pre-aging nickelates across various voltage regimes are different from those of the α-nickelates and β-nickelates, as can be seen from the ratios of the capacity contributions from the 3 regions of the discharge curves listed in Table 5 below. To facilitate comparison of the capacity contributions from different voltage regimes, the discharge curves of the nickelates are divided into 3 different regions, namely 1, 2 and 3, corresponding to OCV to 1.63V, 1.63V to 1.45V and 1.45V to 1.00V, respectively. These regions are graphically depicted in Fig.21 middle.

[0214] Table 5

[0215]

[0216]

[0217] Due to the capacity contribution of the unique plateau at 1.85-1.8 V, the ratio of capacity contribution from zone 2 to that of zone 1 is significantly in the lower range of 7.3-9.0 for both the nickelates without pre-ageing and the nickelates with LiOH pre-ageing, while the capacity contributions of α-nickelates and β-nickelates are above 10. For both the nickelates without pre-ageing and the nickelates with LiOH pre-ageing, the percentage of capacity contribution from zone 1 is between 7.4% and 10.4% in all 3 zones, while the percentage of capacity contribution of α-nickelates and β-nickelates is in the range of 2.3% to 6.6%.

Claims

1. A sodium-deionized nickelate material, the cathode material having an X-ray diffraction (XRD) pattern, the XRD pattern comprising a first peak of about 11.9°-14°2θ, a second peak set of about 18°-22°2θ, a third peak of about 36.1°-38.6°2θ, a fourth peak of about 41°-44.2°2θ, a fifth peak of about 55.7°-58.9°2θ, a sixth peak of about 65°-67.3°2θ, and a seventh peak of about 69.5°-71.3°2θ.

2. A sodium-desorbed nickelate material, the cathode material having an X-ray diffraction (XRD) pattern, the XRD pattern comprising a first peak of about 11.3°-14.6°2θ, a second peak set of about 17.3°-22.3°2θ, a third peak of about 23.8°-25.9°2θ, a fourth peak of about 27.2°-28.2°2θ, a fifth peak of about 36.2°-37.7°2θ, a sixth peak of about 40°-44°2θ, a seventh peak of about 55.7°-58.5°2θ, an eighth peak of about 65.2°-67.3°2θ, and a ninth peak of about 69.5°-71.1°2θ.

3. The sodium-deionized sodium nickelate material according to claim 1 or 2, wherein the sodium-deionized sodium nickelate material has been deionized by acid leaching.

4. A pre-aged, de-sodiumed nickelate material, the pre-aged, de-sodiumed nickelate material having an X-ray diffraction (XRD) pattern, the XRD pattern comprising a first peak of about 11.9°-13.8°2θ, a second peak of about 17°-19.5°2θ, a third peak of about 24.7°-26.5°2θ, a fourth set of peaks of about 36.3°-39.2°2θ, a fifth set of peaks of about 41.9°-45.7°2θ, a sixth peak of 47.5°-49.5°2θ, a seventh peak of about 50.3°-52°2θ, an eighth peak of about 57.4°-58.7°2θ, and a ninth set of peaks of about 65°-68°2θ.

5. A pre-aged, de-sodiumed nickelate material, the pre-aged, de-sodiumed nickelate material having an X-ray diffraction (XRD) pattern, the XRD pattern comprising a first peak of about 11.1°-14.4°2θ, a second set of peaks of about 17.2°-19.9°2θ, a third peak of about 24.1°-26.0°2θ, a fourth set of peaks of about 35.8°-39.3°2θ, a fifth set of peaks of about 43.4°-45.4°2θ, a sixth peak of 47.7°-49.4°2θ, a seventh peak of about 56.8°-59.6°2θ, an eighth peak of about 62.8°-64.5°2θ, a ninth peak of about 65°-67.4°2θ, and a tenth peak of about 68.1°-69.2°2θ.

6. The pre-aged de-sodiumed nickelate material according to claim 4 or 5, wherein the pre-aged de-sodiumed nickelate material has been prepared by pre-aging a de-sodiumed nickelate precursor using a pre-aging solution, wherein the pre-aging solution comprises one or more agents selected from the group consisting of hydroxides.

7. The pre-aged, desodiumed nickelate material of claim 6, wherein the pre-aging solution comprises a hydroxide selected from the group consisting of LiOH, NaOH, and other alkali and alkaline earth hydroxides.

8. The pre-aged, desodiumed nickelate material of any one of claims 6 to 7, wherein the pre-aging solution has a hydroxide concentration of about 0.005 M to about 1 M.

9. The pre-aged de-sodiumed nickelate material of any one of claims 6 to 8, wherein the ratio of the pre-aging solution to the de-sodiumed nickelate precursor is from about 1 mL / g to about 100 mL / g.

10. The pre-aged de-sodiumed nickelate material of any one of claims 6 to 9, wherein the de-sodiumed nickelate precursor is pre-aged for about 1-60 minutes.

11. The pre-aged de-sodiumed nickelate material of any one of claims 6 to 10, wherein the pre-aged de-sodiumed nickelate material is pre-aged at a temperature of about 0°C to about 40°C.

12. A method of producing a pre-aged, desodiumated nickelate material, the method comprising: i) contacting sodium nickelate with an acid solution to produce acid-leached, de-sodiumed nickelate; as well as ii) contacting the acid-leached desodiumed nickelate with a pre-aging solution comprising a hydroxide to produce the pre-aged desodiumed nickelate material.

13. The method of claim 12, wherein the acid-leached desodiumed nickelate has the formula Na x NiO2, where 0≤x≤0.

2.

14. The method of claim 12 or 13, wherein the acid solution comprises an acid selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, hydrobromic acid, hydroiodic acid and perchloric acid.

15. The method of claim 14, wherein the acid is sulfuric acid.

16. The method of any one of claims 12 to 15, wherein the acid is present in a concentration of about 0.01 M to about 10 M.

17. The method of any one of claims 12 to 16, wherein step i) is performed for a period of time in the range of about 1 minute to about 60 hours.

18. The method of any one of claims 12 to 17, wherein step i) is performed at a temperature of about -5°C to about 20°C.

19. The method of any one of claims 12 to 18, wherein step i) is performed using about 10 mL to about 200 mL of acid solution per gram of sodium nickelate.

20. The method of any one of claims 12 to 19, wherein the pre-aging solution comprises a hydroxide selected from the group consisting of LiOH, NaOH, Ca(OH)2 and other alkali metal hydroxides and alkaline earth metal hydroxides.

21. The method of any one of claims 12 to 20, wherein the hydroxide is present at a concentration of about 0.005 M to about 1 M.

22. The method according to any one of claims 12 to 21, wherein step ii) is performed for a time period in the range of about 1-60 minutes.

23. The method of any one of claims 12 to 22, wherein step ii) is performed at a temperature of about 0°C to about 40°C.

24. A pre-aged, desodiumated nickelate material prepared by the method according to any one of claims 12 to 23.

25. An alkaline cathode composition comprising the pre-aged desodiumated nickelate material of any one of claims 4 to 11 and 24 and electrolytic manganese dioxide.

26. The composition of claim 25, wherein the ratio of nickel to manganese is from 99:1 to 1:99 by weight.

27. An alkaline cathode composition comprising the pre-aged de-sodiumed nickelate material of any one of claims 4 to 11 and 24, electrolytic manganese dioxide, graphite and a binder.

28. The composition of claim 27, wherein the pre-aged desodiumated nickelate material is present in an amount of about 8.8-45.1 wt.%, the electrolytic manganese dioxide is present in an amount of about 48-84.3 wt.%, the graphite is present in an amount of about 3-8 wt.%, and the binder is present in an amount of about 0.1-1.0 wt.%.

29. The composition of claim 27, wherein the pre-aged desodiumed nickelate material and the EMD together are present in an amount of about 92-97 wt.%, the graphite is present in an amount of about 3-8 wt.%, and the binder is present in an amount of about 0.1-1.0 wt.%.

30. A sodium-deionized nickelate material comprising the following phases: i) 15-50 wt% NiO2; ii) 20-60 wt% of β-NiOOH; iii) 0-25 wt% H 0.61 NiO2(H2O) 0.91 ;as well as iv) 0-25 wt% Na 0.33 NiO2(H2O) 0.54 .

31. A sodium-free nickelate material having the formula Na x NiO2(H2O) z , where x = 0.01-0.05, and z = 0.2-1.

1.

32. A nickelate material comprising the following phases: i) 4-62 wt% Na 0.33 NiO2(H2O) 0.54 ; ii) 30-80 wt% (Li 0.39 Ni 0.01 )(NiO2) and / or (Li 0.49 Ni 0.01 )(NiO2) and / or (Li 0.45 Ni 0.05 )(NiO2); and iii) 0-50 wt% of β-NiOOH.

33. A nickelate material comprising the following phases: i) 80-85 wt% Na 0.33 NiO2(H2O) 0.54 ;as well as ii) 15-20 wt% of β-NiOOH.

34. A nickelate material having the formula Na x Li y NiO2(H2O) z , where x = 0.01-0.05, y = 0.15-0.45, and z = 0.1-0.

8.

35. A nickelate material that exhibits three discharge plateaus relative to a Zn / ZnO reference electrode during discharge at a discharge rate of 10 mA / g to a voltage of 1.0 V.

36. The nickelate material of claim 35, wherein the nickelate material exhibits a discharge plateau of about 1.85-1.80 V during discharge at a discharge rate of 10 mA / g.

37. The nickelate material of claim 35, wherein the nickelate material exhibits a discharge curve relative to Zn / ZnO at a discharge rate of 10 mA / g, wherein the discharge curve depicts voltage versus specific capacity; wherein the specific capacity is divided into a first region of OCV to 1.63V; a second region of 1.63V to 1.45V; and a third region of 1.45V to 1.00V; wherein the capacity contribution of a given region is the difference between the capacity at the end of the region and the capacity at the beginning of the region; and i) a ratio of the capacity contribution of the second region to the capacity contribution of the first region is less than 10; or ii) the capacity contribution of the first zone relative to the total capacity contribution of the first zone, the second zone and the third zone is at least 7.0%.

38. A composition comprising particles composed of a nickelate material, wherein the particles comprise i) an inner layer comprising a nickelate that has not been pre-aged with a hydroxide; and ii) an outer layer comprising a nickelate that has been pre-aged with a hydroxide.

39. An alkaline electrochemical cell comprising the nickelate material of any one of claims 1 to 11, 24, or 30 to 37 or the composition of any one of claims 25 to 29 or 38.

Citation Information

Patent Citations

  • Nickelate cathode materials

    US11560321B2

  • Digital signal processor with a byte DMA controller

    US6816922B2